THE POSSIBILITY OF APPLYING AN OBEYA SYSTEM IN MAKING PRODUCTION AND OPERATIONS DECISIONS - Alaa Abdulsalam Mustafa (Galaxy International Interdisciplinary Research Journal, 2024)
The purpose of the research is to identify the Obeya system and its role in making production and operations decisions at the General Company for the Iraqi Automotive and Equipment Manufacturing Company. A questionnaire form was developed to ensure the existence of a relationship between the research variables, and based on the comprehensive inventory method, (143) questionnaire forms were distributed in the company, and their data were analyzed using the (AMOS) program .